Tinjauan Pengaruh Literasi Keuangan, Pendapatan, Risiko Investasi, Sikap Investasi, dan Pengetahuan Investasi terhadap Minat Berinvestasi - Anisa Olinda Hanum,; Kusumawati, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of financial literacy, income, investment risk, investment attitude, and investment knowledge on investment interest of students of Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (FEB UMS). The research method used is a quantitative approach with data processing using SPSS. Primary data was obtained through a closed-ended questionnaire with five-point Likert scale, which was distributed to active students of FEB UMS who had completed at least two semesters. The sample was selected through purposive sampling. Data analysis includes validity, reliability, classical assumptions, multiple linear regression, F-test, coefficient of determination (R²) and t-test. The results showed that income, investment risk, investment attitude, and investment knowledge have a significant effect on investment interest, while financial literacy has no effect on investment interest. Income, investment risk, investment attitude, and investment knowledge that are positively perceived by students can increase their investment interest. This study provides an empirical contribution on the factors that influence investment interest, so it can be a reference in the development of financial literacy and strategies to increase investment interest among students.